Unprecedented Spring 2020 Ozone Depletion in the Context of 20 Years of Measurements at Eureka, Canada. Issue 8 (26th April 2021) - Bognar, Kristof; Alwarda, Ramina; Strong, Kimberly; Chipperfield, Martyn P.; Dhomse, Sandip S.; Drummond, James R.; Feng, Wuhu; Fioletov, Vitali; Goutail, Florence; Herrera, Beatriz; Manney, Gloria L.; McCullough, Emily M.; et al.
Abstract: In the winter and spring of 2019/2020, the unusually cold, strong, and stable polar vortex created favorable conditions for ozone depletion in the Arctic. Chemical ozone loss started earlier than in any previous year in the satellite era and continued until late March, resulting in the unprecedented reduction of the ozone column. The vortex was located above the Polar Environment Atmospheric Research Laboratory in Eureka, Canada (80°N, 86°W) from late February to the end of April, presenting an excellent opportunity to examine ozone loss from a single ground station. Measurements from a suite of instruments show that total column ozone was at an all‐time low in the 20‐year data set, 22–102 DU below previous records set in 2011. Ozone minima (<200 DU), enhanced OClO and BrO slant columns, and unusually low‐HCl, ClONO2, and HNO3 columns were observed in March. Polar stratospheric clouds were present as late as 20 March, and ozonesondes show unprecedented depletion in the March and April profiles (to <0.2 ppmv). While both chemical and dynamical factors lead to reduced ozone when the vortex is cold, the contribution of chemical depletion (based on the variable correlation of ozone and temperature) was exceptional in spring 2020 when compared to typical Arctic winters. Mean chemical ozone loss over Eureka was estimated to be 111–126 DU (27%–31%) using April measurements and passive ozone from the SLIMCAT chemical transport model. While absolute ozone loss was generally smaller in 2020 than in 2011, percentage ozone loss was greater in 2020. Plain Language Summary: While an ozone hole forms over Antarctica every year, the Arctic typically does not experience such dramatic ozone loss. The chlorine and bromine (halogen) reactions that destroy ozone require very low temperatures that are rarely observed in the Arctic stratosphere. The winter and spring of 2019/2020, however, was unusually cold in the Arctic, and consequently, a large amount of ozone was destroyed by halogen chemistry. To understand the behavior of ozone in spring 2020, we use measurements from the Polar Environment Atmospheric Research Laboratory in Eureka, Canada. Eureka (at 80°N) is one of the northernmost research stations in the world, and thus an ideal location to observe ozone loss. Spring 2020 ozone minima were lower than any in the 20‐year data set, and ozone destruction was ongoing until the end of March, which is rare in the Arctic. While ozone concentrations are largely determined by circulation patterns in the Arctic stratosphere, chemistry in spring 2020 was a much larger factor than usual. Halogen chemistry destroyed 27%–31% of the total ozone, compared to about 10% in a typical winter. The only year on record with comparable ozone loss is 2011, and a larger percentage of the ozone column was lost in 2020. Key Points: Record low ozone columns (<200 DU) were observed over Eureka in spring 2020 Limited dynamical resupply of ozone and chemical destruction both contributed to reduced ozone columns Mean chemical ozone loss of 111–126 DU (27%–31%) represents similar absolute loss and greater relative loss compared to that in spring 2011